2015
DOI: 10.37897/rmj.2015.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology: Concepts and Applications in Medicine

Abstract: Objectives. To assess the concepts of teledermatology (TD), a subspecialty of dermatology and one of the most common applications of telemedicine. Material and methods. This systematic review, totaling 32 works, is aimed to evaluate the advantages and limitations of teledermatology, which can be delivered in two ways: real-time (synchronous), using videoconference technology, and store-and-forward (SAF) methods (aynchronous), using digital images via internet, a cheaper and more convenient modality for the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Additionally, despite having a limited number of individuals, the study showed that the degree of skin hydration in subjects taking the EY ingredient was inversely proportional to their age, and those who showed the most obvious effect were the women under 50 years (Figure 2b). A similar pattern was previously shown in other studies with other moisturizing ingredients [17]. Although the mechanism by which the ingredient increases skin hydration is unknown, it may be due in part to the ability of one of the tested ingredient's components, asiaticosides, to increase the expression of Aquaporin-3 (AQP3) [28].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, despite having a limited number of individuals, the study showed that the degree of skin hydration in subjects taking the EY ingredient was inversely proportional to their age, and those who showed the most obvious effect were the women under 50 years (Figure 2b). A similar pattern was previously shown in other studies with other moisturizing ingredients [17]. Although the mechanism by which the ingredient increases skin hydration is unknown, it may be due in part to the ability of one of the tested ingredient's components, asiaticosides, to increase the expression of Aquaporin-3 (AQP3) [28].…”
Section: Discussionsupporting
confidence: 83%
“…The skin type was categorized as follows: very dry skin was characterized by corneometer units below 30, dry skin between 30 and 45.5, and sufficiently hydrated skin higher than 45.5 corneometric units (c.u.) [17]. Since only one person presented very dry skin, only two subgroups were defined (dry to very dry skin type and sufficiently hydrated).…”
Section: Skin Moisturizationmentioning
confidence: 99%
“…After 50 minutes from emulsions application the corneometry values decreased. In contrast, the Authors [5] obtained opposite results, because the maximum hydration was observed after one hour from application.…”
Section: Resultsmentioning
confidence: 89%
“…Each change of the dielectric constant subsequent to the modification of skin hydration results in an impaired calculated capacitance of a capacitor. The skin hydration degree values are in the range 0-130 arbitrary units (AU) [5].…”
Section: Determination Of Skin Capacitancementioning
confidence: 99%
“…Skin moisture was measured on the face and the volar forearm, 5 cm distal to the elbow, using a Corneometer®CM 825 (C+K, Germany). This device is well known for being able to estimate the moisture content in the stratum corneum (SC) 55 . All electrical phenomena are caused by electric charges, with capacitance indicating the ability to store these charges, and when the anode plate of a probe is charged, it creates an electric field in between.…”
Section: Measurement Of Skin Hydrationmentioning
confidence: 99%